A single espresso, please! Rationalizing espresso price dispersion across Italian cities - Flavio Delbono; Gemma Dipoppa; Luca Lambertini; Carlo Reggiani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
This paper aims at providing an explanation of the observed espresso price dispersion across major Italian cities. The empirical evidence suggests a positive relationships between the average espresso price in a city and the number of coffee shops (normalized for the adult population) operating in that city. This finding is shown to be robust after controlling for GDP per capita and consumers.price index. We provide an interpretation of the empirical findings relying on a model of price competition delivering a continuum of Nash equilibria, where firms adjust the mark-up to offset the negative effect of any increase in their number.
Keywords: L11; L13; L66; 330